Hizkuntzaren ikaskuntzaren inguruko teoriak eta didaktika - Zubiri Lujanbio, Juan José (Huarte de San Juan. Filología y Didáctica de la Lengua, 2003)
This paper is a brief overview of the most relevant methodological currents relative to learning and acquisition in general and, in more specific terms, to the theories that have placed special emphasis on the learning and acquisition of languages. After examining each of the theories, I analyse the relationship and influence they have had on learning and on language didactics of both mother tongue (L1) and second language (L2). Considering that each of these theories reflect a particular approach to acquisition and teaching and learning of a language, I follow on to assess the impact of these on the school or to put it differently, I analyse to which extend these theories provide effective proposals for mainstream teaching and learning in schools.